Disruptive innovation in business and finance in the digital world - Choi, J. Jay; Ozkan, Bora (Bingley, U.K. : Emerald Publishing Limited, 2019)
Digital disruption is ubiquitous and has changed both the way businesses operate and the way people live. Disruption caused by innovation affects firms across multiple industries, from financial services to industrial firms, business processes to payment systems, manufacturing to supply chains. Further, scholars hear more and more about artificial intelligence (AI), big data, machine learning, blockchain, and fintech as examples of contemporary manifestations of disruptive technology that will profoundly influence disciplines beyond business and finance, such as law, health care and government. Global extensions of these technologies and innovations challenge the efficacy and boundaries of law. Indeed, disruptive innovations are potentially change the way we consider the future as humans versus some super artificial intelligence.This volume contains fourteen articles split across four parts, exploring the debate around the topics of fintech, AI, blockchain, and cryptocurrency. Featuring a cast of global contributors, this is an unmissable volume exploring the most current research on digital innovation in the financial and business worlds.
Keywords: Disruptive technologies; Digital divide; Business & Economics -- Finance -- General; Finance